Scrutiny of income related drivers of energy poverty: A global perspective. (October 2021) - Husnain, Muhammad Iftikhar ul; Nasrullah, Nasrullah; Khan, Muhammad Aamir; Banerjee, Suvajit
Abstract: This paper intends to explore the roles of a variety of income-related attributes of the problem of energy poverty which should be considered in the policy-making for alleviating various constraints for essential access of the people to useable energy. This inquiry scrutinizes the drivers of energy poverty in the settings of development stages by using the data of 190 countries grouped under low-income, middle-income, and high-income brackets from 1991 to 2019. For being a multifaceted issue, this study adopts the definition of access to modern energy facilities in the form of electricity consumption as a popular proxy for energy poverty. The empirical model conducts advanced panel cointegration methods i.e., panel ARDL based on pooled mean group and panel quantile regression. The findings of the study illustrate that the influence of different factors on access to electricity is heterogeneous along with the three panels of countries. The derived heterogeneity of employment, inflation, GDP, education, stock market returns and liquid liabilities over energy poverty is due to the diversified demographics of the low-income, middle-income, and high-income countries. The study found that the stage of economic development is a key factor in the determination of energy poverty, and this has important policy implications at the global level while accounting for the income attributes of the relevant countries. Highlights: Income related drivers of energy poverty are studied in a global perspective. The stage of economic development is a key factor in the determination of energy poverty. Financial development shows a negative correlation with access to electricity. Policy frameworks are needed for broadening the electricity provision network.